A Journal of the Santa Fe Expedition under Colonel Doniphan : Exploration and Conquest in Northern Mexico. - Robinson, Jacob S. (Narrative Press, the, 2004)
Mr. Robinson was with Colonel Doniphan's expedition against Mexico in 1846 and being an easterner, saw the Mexicans and Navajo and the landscape with fresh eyes. He felt the entire expedition was ill managed. While the military significance of the expedition is indisputable, he was often more captivated with the scenes and the people he encountered than by their war with Mexico.